Analisis Perbedaan Peningkatan Berat Badan Pada Ibu Akseptor Kontrasepsi Suntik Satu Bulan Dan Tiga Bulan - Ambarwati, Winarsih Nur; Santoso, Rifki Yulinanda Budi (Jurnal Berita Ilmu Keperawatan, 2019)
There are many aspects of reproductive health that must be assessed, one of which is the use of contraceptive methods. The most widely used contraceptive method in Indonesia is injection contraception. Injectable contraception has many advantages but also detrimental effects which are affect to women’s health. Weight gain is the most reported side effect by acceptors.This study aims to analyze the differences in maternal weight changes in users of injection contraception for one month and three months.This type of research is quantitative by using descriptive comparative methods with time series research designs. The sampling technique used purposive sampling. Respondents were 60 mothers who were divided into two groups, 30 mothers using one-month injection contraception and 30 mothers using three months of injection contraception. Respondents in the two groups were measured every month for six months. Instruments for recording body weight are observational sheets and CAMRY digital scales. The statistical analysis used was paired t-test and independent t-test.The results of paired t-test, at bodyweight before and after six months, showed that acceptors of one-month injection contraception were -4.038 with a p-value of 0,000 (p